Risk attitudes and the big five personality traits: A study on construction project practitioners in Malaysia - Lee, Chia Kuang; Foo, Mei Yit (Taylor & Francis, 2020)
Risk management often applies in any decision making process to ensure success of an objective. However, many organizations fail to realize the importance of such knowledge, especially in high risk and complex industries in construction. The decision made while taking uncertainty into account varies among individuals based on their attitudes. Hence, their perspectives towards uncertainty may be the determinant to ensure success in a project. As risk attitudes and perception varies among individuals, so does personality. Henceforth, this study aims to investigate the relationship of the factors in the Big Five theory in influencing risk attitude, by using the Big Five Inventory (BFI) model and the Domain Risk-attitude scale, in order to determine individuals’ personality based on the five dimensions for both categories. The proposed model was tested on 70 decision makers, particularly project practitioners specialize in the construction industry in Malaysia. Partial Least Squared Structural Equation Modelling (PLS-SEM) was used to investigate both variables based on the objectives. The results showed that all variables but one has a significant effect towards risk attitude, where extraversion has the most effect towards risk attitude. All factors of the Big Five except neuroticism reacts positively towards risk attitude. The study of relationship between personality traits and risk taking will signify the vast variations of how every decision maker will choose to respond to uncertainty depending on their respective human behaviour. Such understanding helps in the development of a comprehensive risk management plan.